Predictors of long-term prognosis based on measurements achieved after 9-week hybrid telerehabilitation in heart failure patients – a subanalyis of the TELEREH-HF RCT. (3rd October 2022) - Piotrowicz, E; Pencina, M; Kowalik, I; Orzechowski, P; Banach, M; Glowczynska, R; Zareba, W; Opolski, G; Szalewska, D; Pluta, S; Kalarus, Z; Irzmanski, R; et al.
Abstract: Background: Predicting prognosis in heart failure (HF) is of major importance. The purpose of the study was to define predictors influencing long-term cardiovascular mortality or HF hospitalization ("composite outcome") based on clinical status and measurements obtained after the 9-week hybrid comprehensive telerehabilitation (HCTR) programme. Methods: This analysis is based on TELEREH-HF multicenter, randomized trial that enrolled 850 HF patients (NYHA I-III; left ventricular ejection fraction [LVEF]≤40%). Patients were randomized 1:1 to 9-week HCTR plus usual care (development sample) or usual care only (validation sample) and followed for 12–24 months for development of the composite. Results: The predictors of our composite were: non-ischaemic etiology of HF, diabetes, higher serum level of: N-terminal prohormone of brain natriuretic peptide, creatinine, and high-sensitivity C-Reactive Protein; low carbon dioxide output at peak exercise, high minute ventilation and breathing frequency at maximum effort in cardiopulmonary test; increase of delta of average heart rate in 24h-ECG Holter monitoring, lower LVEF and patients' non-adherence to HCTR. The model discrimination C-index=0.795 and decreased to 0.755 on validation (Table 1). The 2-year risk of the composite was 48% in the top tertile versus 5% in the bottom tertile (Figure 1). Conclusion: Risk factors collected at the end of the 9-week telerehabilitaion period did an excellent job in stratifying patients based on their 2-year risk of the composite outcome. Patients in the top tertile had an almost ten-fold higher risk compared to patients in the bottom tertile. Adherence to treatment but not peakVO2 or quality of life were significantly associated with the outcome. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Centre for Research and Development, Warsaw, Poland